DETERMINANTS OF THE OPTICAL ILLUSIONS EFFECT ON THE DALEM AGENG PRABAYEKSA ROOF, DALEM MANGKUBUMEN AREA, YOGYAKARTA - Muhammad Riyan Subastian; Tarcicius Yoyok Wahyu Subroto (Built Environment Studies, 2023)
Javanese buildings can be understood both physically and non-physically, one of them is the Dalem Ageng Prabayeksa which is in the Dalem Mangkubumen complex. This building has the most important and sacred position in the complex with the uniqueness of the hip roof (limasan), which cannot be found in other hip roof buildings. This study focuses on optical illusions that occur on the roof of the building in front (south) and rear (north) views using explorative descriptive methods. Optical illusions that affect visual perception occur because of the imaginary perspective lines formed from the diagonals of the roof of the building so that an illusion is created that make the roof of the building look wider and taller than it should be. The roof of the building is also formed from proportions that are in accordance with the reference for the building as a house and the building as a place of worship (temples) which supports how optical illusions can occur so that a visual perspective and meaning behind the design of the roof appears which makes sense and is in line with the position of the Dalem Ageng Prabayeksa building as the most important and sacred building in the Dalem Mangkubumen complex.